2005
DOI: 10.1165/rcmb.2004-0253oc
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Human Nasal Vascular and Sinusoidal Endothelial Cells from the Inferior Turbinate

Abstract: The vast heterogeneity of endothelial cells (EC) in various organs necessitates isolation of EC from the relevant organs when defining mechanisms of site-specific pathologies. We report a novel finding that describes the presence of two heterogeneous populations of human nasal microvascular EC isolated from the inferior turbinate. Light and electron microscopy, flow cytometric analysis, and immunocytochemistry analysis demonstrated that one EC population exhibited the classic vascular endothelial markers with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The degree to which endothelial function varies among arterioles, capillaries and venules is regarded as segmental heterogeneity (Boegehold, 1998). While the nature and significance of such heterogeneity in the peripheral vasculature has been well acknowledged (Garlanda and Dejana, 1997; Ribatti et al, 2002; Aird, 2003; Gebb and Stevens, 2004; Holmen et al, 2005), much less attention has focused on central nervous system (CNS) microvessels (Ge et al, 2005). This oversight may stem from the fact that capillaries comprise the vast majority of the CNS microvascular surface area (Abbott et al, 2006) ‐ a situation leading to the terms capillaries and microvessels often being used interchangeably when referring to the CNS microvasculature (Ge et al, 2005).…”
mentioning
confidence: 99%
“…The degree to which endothelial function varies among arterioles, capillaries and venules is regarded as segmental heterogeneity (Boegehold, 1998). While the nature and significance of such heterogeneity in the peripheral vasculature has been well acknowledged (Garlanda and Dejana, 1997; Ribatti et al, 2002; Aird, 2003; Gebb and Stevens, 2004; Holmen et al, 2005), much less attention has focused on central nervous system (CNS) microvessels (Ge et al, 2005). This oversight may stem from the fact that capillaries comprise the vast majority of the CNS microvascular surface area (Abbott et al, 2006) ‐ a situation leading to the terms capillaries and microvessels often being used interchangeably when referring to the CNS microvasculature (Ge et al, 2005).…”
mentioning
confidence: 99%
“…However, both genetic factors and environmental conditions determine the phenotype of any given EC. While microarray surveys of cultured ECs provide strong evidence that some aspects of cell phenotype are not dependent on environmental cues [6][7][8]31], studies comparing freshly isolated and cultured cells clearly indicate that the microenvironment plays a role in maintaining other phenotypic features. Durr et al [70] used proteomics to quantify the difference in protein expression by freshly isolated vs. cultured rat lung ECs; of 450 proteins identified in a rigorous analysis, 41% of proteins that were detected in vivo were not detected in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that endothelial heterogeneity exists within an organ. For example, the microvasculature of the nasal mucosa consists of two EC types, termed "vascular", lying directly beneath the epithelium, and "sinusoidal", located around the nasal glands, with significant differences in respective gene expression profiles [7]. Within the heart, endocardial endothelium expresses high levels of transcripts involved in electrophysiological functions, differing from microvascular endothelium which up-regulates transcripts related to angiogenesis [8].…”
Section: Introductionmentioning
confidence: 99%
“…BECs treated in the same manner as above with IgG F(ab′) 2 fractions were also double stained by immunofluorescence as previously described 22. Staining with the above‐mentioned TLR antibodies was followed by labeling with Texas red–conjugated secondary goat‐anti‐mouse antibodies and FITC‐conjugated CK‐19 (DAKO, Glostrup, Denmark).…”
Section: Methodsmentioning
confidence: 99%